Bioequivalence and pharmacodynamics of a generic dabigatran etexilate capsule in healthy Chinese subjects under fasting and fed conditions - Xin Li; Lihua Liu; Bing Xu; Qian Xiang; Yuan Li; Ping Zhang; Yangyang Wang; Qiufen Xie; Yong Mao; Yimin Cui (Wiley, 2020)
Abstract To assess bioequivalence of a generic dabigatran etexilate capsule in healthy Chinese subjects under fasting and fed conditions. This was an open‐label, single‐center, randomized four‐period crossover study with a 7‐day washout period. A single oral dose of 150 mg generic dabigatran etexilate capsule (test drug) or a commercial dabigatran etexilate capsule (Pradaxa®, reference drug) was given to healthy volunteers under the fasting and fed conditions. Plasma concentrations of total and free dabigatran were detected using a validated HPLC‐MS/MS method. A noncompartmental method was used for pharmacokinetic analysis and established coagulation assays were applied for pharmacodynamic analysis. The 90% CIs of the test/reference ratios of Cmax, AUC0‐t, and AUC0‐∞ for the total dabigatran concentration were 92.57%‐106.58%, 91.63%‐106.32%, and 92.54%‐106.17%, respectively, under fasting condition, and 99.30%‐110.74%, 98.58%‐105.37%, and 97.75%‐103.99%, respectively, under fed conditions. The 90% CIs of the ratios of the parameters for the free dabigatran were 93.18%‐106.98%, 92.13%‐107.10%, 92.89%‐106.48%, respectively, under fasting condition, and 100.05%‐110.89%, 99.37%‐106.23%, 97.59%‐103.98%, respectively, under the fed condition. Additionally, the upper limit of the 90% CIs for σWT/σWR was below 2.5. There were no significant differences in the coagulation parameters including thrombin clotting time, activated partial thromboplastin time, and anti‐IIa activity between the two preparations. The generic dabigatran etexilate capsule is bioequivalent to the brand‐named product in healthy Chinese volunteers under fasting and fed conditions. The two products have comparable pharmacodynamic parameters, with a good safety profile. In addition, food intake influences absorption of both products in a similar way.